Dendritic cells and Brucella spp. interaction: the sentinel host and the stealthy pathogen - Avila-Calderón, Eric Daniel; Flores-Romo, Leopoldo; Sharon, Witonsky; Donis-Maturano, Luis; Becerril-García, Miguel Angel; Arreola, Ma Guadalupe Aguilera; Reynoso, Beatriz Arellano; Güemes, Francisco Suarez; Contreras-Rodríguez, Araceli (Folia microbiologica, 2020)
As dendritic cells (DCs) are among the first cells to encounter antigens, these cells trigger both innate and T cell responses, and are the most potent antigen-presenting cells. Brucella spp., which is an intracellular facultative and stealthy pathogen, is able to evade the bactericidal activities of professional phagocytes. Several studies have demonstrated that Brucella can survive and replicate intracellularly, thereby provoking impaired maturation of DCs. Therefore, the interaction between DCs and Brucella becomes an interesting model to study the immune response. In this review, we first will describe the most common techniques for DCs differentiation in vitro as well as general features of brucellosis. Then, the interaction of DCs and Brucella, including pathogen recognition, molecular mechanisms of bacterial pathogenesis, and intracellular trafficking of Brucella to subvert innate response, will be reviewed. Finally, we will debate diversity in immunological DC response and the controversial role of DC activation against Brucella infection.
Keywords: interakce hostitele a patogenu; dendritické buňky; Animals; Brucellosis; Humans; Brucella; Cytoplasm; lidé; brucelóza; zvířata; Host-Pathogen Interactions; Mice; cytoplazma; Dendritic Cells; myši